A rare case of emphysematous pyelonephritis in a renal transplant patient. (December 2016) - Narcisse, Dennis; Agarwal, Manyoo; Hancock, Michael; Wells, Daniel; Sands, Christopher
Emphysematous pyelonephritis (EPN) is a rare life-threatening complication of a properly functioning renal allograft leading to potential graft loss and hemodialysis. Currently, no clear management guidelines exist in these clinically challenging immunosuppressed renal transplant recipients. We report a case of a 62-year-old woman who presented with class 4 EPN and was managed with intravenous antibiotics and nephrectomy at our medical center.